VD_FINDINFO Jug / 2015 / 310 vom 5. Mai 2014 - VD Tribunal cantonal (2014)
DEMANDE ADRESSÉE À L'AUTORITÉ, RÉVISIONDÉCISION, DÉCISION D'IRRECEVABILITÉ, DÉFENSE D'OFFICE | 135 CPP (CH), 410 al. 1 let. a CPP (CH), 428 al. 1 CPP (CH)